Non-resolving, recurrent and chronic central serous chorioretinopathy: available treatment options - Sartini, Francesco (Eye (Lond), 2019)
Central serous chorioretinopathy is one of the most frequent causes of vision reduction among middle-aged men. This disease usually has a self-limiting course, but sometimes it lasts more than 4–6 months or a second episode follows a complete resolution of the first one. Nevertheless, to date no consensus exists about the duration threshold and therapy protocols for these non-resolving central serous chorioretinopathy. Treatment as half-dose and half-fluence photodynamic therapy, subthreshold micropulse laser treatment, mineralocorticoid receptor antagonists, intravitreal anti-angiogenic drugs, transpupillary thermal therapy, anti-androgenic drugs, methotrexate, Rifampicin and melatonin are described in this review. Complications are very uncommon but end-point results like central macular thickness reduction and best-corrected visual acuity improvement are difficult to compare among different therapeutic modalities due to different duration of follow-up and lack of homogeneity in patient recruitment. The aim of this review is focusing on treatment modalities for these chronic forms with comprehensive recent management updates according to latest clinical trial results.